USP12 promotes antiviral responses by deubiquitinating and stabilizing IFI16 - Fu, Yuling; Zhan, Xiaoxia; You, Xiaolong; Nie, Dingnai; Mai, Haiyan; Chen, Yitian; He, Shitong; Sheng, Junli; Zeng, Zhijie; Li, Hongwei; Li, Jinlong; Hu, Shengfeng (PLoS pathogens, 2023)
Deubiquitinating enzymes (DUBs) regulate antiviral immune response through targeting DNA sensor signaling pathway members. As one of the DNA sensors, interferon (IFN)-γ inducible protein 16 (IFI16) play a major role in response to virus infections through activating the canonical STING/TBK-1/IRF3 signaling pathway. Only a few studies discuss the function of DUBs in IFI16-mediated antiviral response. Ubiquitin-specific protease 12 (USP12), which is one of the major members of the USP family, participates in various biological functions. However, whether USP12 regulates the nucleic acid sensor to modulate antiviral immune responses has not yet been elucidated. In this study, we found that knockout or knockdown of USP12 impaired the HSV-1-induced expressions of IFN-β, CCL-5, IL-6, and downstream interferon-stimulated genes (ISGs). Moreover, USP12 deficiency increased HSV-1 replication and host susceptibility to HSV-1 infection. Mechanistically, USP12 inhibited the proteasome-dependent degradation of IFI16 through its deubiquitinase activity, thereby maintaining IFI16 stability and promoting IFI16-STING-IRF3- and p65-mediated antiviral signaling. Overall, our findings demonstrate an essential role of USP12 in DNA-sensing signaling and contribute to the understanding of deubiquitination-mediated regulation of innate antiviral responses.